Recent environmental change and atmospheric contamination on Svalbard as recorded in lake sediments – modern limnology, vegetation, and pollen deposition - Birks, Harry John Betteley; Monteith, Don T.; Rose, Neil L.; Jones, Vivienne J.; Peglar, Sylvia M. (Springer, 2004)
This is the second in a series of nine papers published in this special issue dedicated to recent environmental change on Svalbard. H.J.B. Birks, Vivienne J. Jones, and Neil L. Rose were guest editors of this special issue. Twenty-four lakes on Svalbard were sampled for palaeolimnological studies and are described in terms of their geographical location, catchment characteristics, water chemistry, and flora. No sediment could be retrieved from one of the lakes. There is a close correlation, as detected by redundancy analysis, between lake-water chemistry and catchment variables, particularly bedrock geology and geographical location for 23 lakes. The flora of the lake catchments is statistically related, as shown by canonical correspondence analysis, to bedrock geology, climate (geographical location), and nutrient status (bird impact). Modern pollen assemblages from eleven lakes contain 2–25% far-distance extra-regional pollen. The modern local and regional pollen depositions are dominated by Oxyria digyna, Poaceae, Saxifraga, Salix, and Brassicaceae pollen.